Worldwide trend in research on Candida albicans and cancer correlations: a comprehensive bibliometric analysis - Tang, Shiqin; Xu, Yanyan; Li, Xiaojing (Frontiers in Microbiology, 2024)
Objective: Candida albicans (C. albicans), an opportunistic pathogen, is implicated in the carcinogenesis of various cancers, thereby significantly impacting human health.This study conducts an in-depth analysis of the prevailing research dynamics concerning the relationship between C. albicans and cancer over the past decade, offering a comprehensive overview of the knowledge structure and emerging focal points in this field through bibliometric scrutiny.Methods: A methodical quantitative and visual scrutiny of pertinent literature from the Web of Science Core Collection (WoSCC) spanning the previous decade was carried out employing VOS Viewer and CiteSpace software.